OPTIMALISASI PERTUMBUHAN DAN HASIL EDAMAME (Glycine max L. Merril) MELALUI PEMBERIAN PUPUK NITROGEN DAN EKSTRAK TAUGE KACANG HIJAU - Rahman, Rahman; Tobing, Oktavianus Lumban; Setyono, Setyono (JURNAL AGRONIDA, 2019)
This study was conducted at the experiment garden of Agrotechnology Department, Djuanda University, Bogor, from July to September 2018. The study was aimed at assessing the effects of the application of nitrogen fertilizer and mung bean sprout extract on the growth and production of edamame (Glycine max L. Merril) plants. The experimental design used was a factorial completely randomized design. The first factor is the dose of N fertilizer with four levels, namely without N (0 kg N / ha), a half recommendation of N fertilizer (34.5 kg N / ha), one recommendation of N fertilizer (69 kg N / ha), and one and a half recommendation of N fertilizer (103.5 kg N / ha). The second factor is the concentration of mung bean sprout extract with four levels, namely without mung bean sprout extract (0g tauge extract / l water), a half recommendation of mung bean sprout extract (75g tauge extract/ l water), one recommendation of mung bean sprout extract (150g tauge extract / l water) and one and a half recommendation of mung bean sprout extract (225g tauge extract/ l water). The results showed that the dose of N fertilizer significantly affected the widest leaf area. The concentration of mung bean sprout extract significantly affected the number of shoots at 6 and 7 weeks after planting (MST). Keywords: edamame soybean, N fertilizer, mung bean sprout